Pulmonary Function of Tuberculosis Patients in Medication at Dr. Hasan Sadikin General Hospital Bandung 2013â2014 - Pradipta, Shalahuddin Galih; Suryadinata, Hendarsyah; Setiawan, Setiawan (Althea Medical Journal, 2017)
Â Background: Schizophrenia is a severe and chronic mental disorder that needs a long term treatment and social support. This condition may results in burden and disturbance in the family and society A number of studies have investigated some environmental factors that may potentially lead to schizophrenia. One of many suspected environmental factors is place of born or grew up. This study was conducted to investigate association between place of born or grew up and age of onset of schizophrenia.Methods: This study was conducted from AugustâOctober 2014 at DOTS Policlinic of Dr. Hasan Sadikin General Hospital Bandung. The study population was lung TB patients. The inclusion criteria were 1st category lung TB patients with anti-TB drug treatment on intensive phase. The exclusion criteria were extrapulmonary TB patients, patients with lung surgery history, and patients with asthma or chronic obstructive pulmonary disease (COPD). This study used purposive sampling. The subjects were given a spirometry test where the forced expiratory volume 1 second (FEV1), forced vital capacity (FVC), and their ratio were collected and then interpreted.Results: Among the 60 subjects included in this study, the data showed that 83.4% of the subjects had a decreased pulmonary function consisting of obstructive (6.7%) and restrictive patterns (76.7%).Conclusions: The majority of pulmonary TB patients treated with 1st category anti-TB drugs during intensive phase have a decrease in pulmonary function and most of them have restrictive pattern of pulmonary function.